(untitled) (ACTA MEDICA PERUANA, 2024)
Left lung autotransplantation was practiced in twenty dogs, divides in two groups of ten each one, in the first group the autotransplantation was performed following conventional technics with no conservation of the peribronchial structures, menwhile in the second group the bronchial artiries had been preserved. All of them had bronchoscopy, bronchoespirometry pulmonary X rays and bronchography in the inmediate pre and post operative, in first, second and third months; finally the dogs that survive more than 90 days, were sacrifaiced and necropsied as the ones which died before reaching this period. The surgical technique and the methods for bronchoscopy, bronchoespirometry, radiology and broncography are described. Eleven of twenty animals reached to the final part of the experiment, 4 from the first group and 7 from the second group. High mortality was observed in the first group on the first of 3 weeks due to bronchopneumonia in 2 of them, infarted lung in two and in one disrupture of the bronchial anastomosis. In the second group the major mortality was at the 8th week, all of them due to anaesthetic overdose. The clinic evaluation, radiographies and bronchocopies shown favorable results in the group in which had been conserved the bronchial artery in comparison with the other group. The bronchoespirometry shown that the bronchial irrigation do not have significant effects directly on the functionality of the reimplanted lung.